2019
DOI: 10.1071/sh19018
|View full text |Cite
|
Sign up to set email alerts
|

Management of gonorrhoea in a hospital network: are we following best practice?

Abstract: Background Gonorrhoea is usually managed in community sexual health or general practice, but a proportion of cases present to hospital settings. In this study, we examined how gonorrhoea was managed through a large hospital network and what the implications may be for public health management. Methods: A retrospective chart review was performed of the management of patients with Neisseria gonorrhoeae infection diagnosed at a large Australian healthcare network from January 2015 to May 2018. Documentation rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Other studies have shown that management and documentation of sexual histories are suboptimal for cases that present to ED. 21,22 Merchant et al, 23 in a retrospective study of male adult patients attending the ED with a clinical diagnosis of gonorrhea urethritis, found that 87% received a CDC-recommended empiric treatment for gonorrhea, likely representing the study with the highest compliance to treatment guidelines. Settings with computerized decision support systems may facilitate the management of conditions based on guideline recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that management and documentation of sexual histories are suboptimal for cases that present to ED. 21,22 Merchant et al, 23 in a retrospective study of male adult patients attending the ED with a clinical diagnosis of gonorrhea urethritis, found that 87% received a CDC-recommended empiric treatment for gonorrhea, likely representing the study with the highest compliance to treatment guidelines. Settings with computerized decision support systems may facilitate the management of conditions based on guideline recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…In a small retrospective study in a single ED in the United States, Kane et al 14 found even lower rates of adherence to treatment guidelines for the management of gonococcal infections of 40%. Other studies have shown that management and documentation of sexual histories are suboptimal for cases that present to ED 21,22 . Merchant et al, 23 in a retrospective study of male adult patients attending the ED with a clinical diagnosis of gonorrhea urethritis, found that 87% received a CDC-recommended empiric treatment for gonorrhea, likely representing the study with the highest compliance to treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Loo et al uncover suboptimal management of gonorrhoea in a hospital network in Australia, reminding us of the need for a concerted, broad public health response involving multiple stakeholders including hospital systems, if we are to control this epidemic. 12 They examined five parameters of care:…”
Section: Understanding Ng Case Managementmentioning
confidence: 99%